Agapetes D. Don Ex G. Don - Tony Conlon (Sibbaldia, 2015)
The Royal Botanic Garden Edinburgh (RBGE) holds a number of collections of the family Ericaceae (Conlon, 2010; 2012). One of these is the genus Agapetes D. Don ex G. Don. An overview of the literature on this genus is given with the distribution and a history of the collection at RBGE. Horticultural information for the cultivation and propagation of the genus is included.